A study of mode-I self-similar dynamic crack propagation using a lattice spring model. (April 2018) - Zhao, Gao-Feng; Xia, Kaiwen
Abstract: The spontaneous crack growth in an infinite domain is studied using the distinct lattice spring model (DLSM). The kinetic energy, strain energy, crack opening, and crack branching during the crack growth are investigated numerically using a simple spring model. The discrete simulation satisfactorily reproduces the experimental observations and the theoretical predictions of the fracture energy increase even without considering the crack tip damage zone and crack bifurcation. Moreover, from analysis of the intrinsic fracture energy release rate, it was concluded that the observed fracture energy increase should originate from the distribution of kinetic energy during self-similar crack growth.